Adolescent immunisation in Africa in the decade of vaccines - Abdullahi, Leila Hussein (Department of Clinical Laboratory Science, 2019)
Rationale: There are many public health benefits of targeting adolescent for immunisation. However, and in many settings, adolescents do not get optimal benefits from immunisation. In the decade of vaccines (2011-2020), adolescent immunisation is a topical subject. An up-to-date and synthesized research on adolescent immunisation is lacking. Overall purpose: The purpose of the PhD thesis was to characterize adolescent immunisation in the decade of vaccines. Research methods: First, we conducted a comprehensive narrative review of the literature (chapter 2) on adolescent immunisation. Then, we conducted systematic reviews (chapters 3 and 4). One of the systematic reviews assessed the strategies to improve uptake of vaccines among adolescents. The other systematic review assessed the knowledge, attitudes and practices of adolescents and their parents and teachers towards immunisation. Finally (chapter 5), we conducted a cross-sectional study to describe the challenges experienced, and lessons learnt during the introduction of national human papillomavirus (HPV) vaccination programmes in Africa. Findings: Adolescents are an important group to target with primary, booster or catch up immunisation. Some global initiatives have advocated for adolescent immunisation. Multiple reasons, among them, lack of knowledge and access to immunisation services are barriers to adolescent immunisation. There exist multiple strategies to improve uptake of vaccines among adolescents. For example, health education, financial incentives, mandatory vaccination, and class-based school vaccine delivery. The evidence suggests that a combination of strategies may be more effective than one strategy alone in enhancing uptake of vaccines by adolescents. Knowledge of vaccines, immunisation and vaccine preventable diseases was found to be suboptimal among key stakeholders of adolescent immunisation in Africa. We found a disconnect between the level of knowledge on immunisation and the uptake of vaccines, an interesting finding that warrants further research in Africa. Six African countries shared the lessons learnt and experiences during the national introduction of HPV vaccination programmes that targeted adolescent girls. There were similarities in the results among the participating countries. The challenges included: logistical coordination, identification of the target population, obtaining political support, integration with other school programmes and stakeholder engagement. A lesson learnt was that schools are a convenient site to access and vaccinate adolescents. Conclusion: Adolescent immunisation is not routinely practiced in many countries. The introduction of HPV vaccines has created an ideal opportunity to build platforms for adolescent immunisation. Research on adolescent immunisation is limited, more so in low and middle-income countries. Existing research shows a combination of strategies can be used to enhance uptake of vaccines among adolescents. Strong advocacy programmes are required to drive the global agenda of adolescent immunisation, particularly in Africa.